Peer Reviews on the Fight against Terrorism a Hidden Success of EU Security Governance? - Raphael Bossong (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This paper provides a first study on use of professional peer reviews by the EU to strengthen the European fight against terrorism. The first part outlines two theoretical approaches to assessing the outcome effectiveness of such peer reviews, namely compliance and learning. Peer reviews can serve both ends and have been increasingly touted as an effective tool to address transnational threats. The second part analyzes the evolution and impact of the EU's peer reviews on the fight against terrorism. Although the first peer review took several years to complete, it was regarded as a striking success that improved mutual trust and the coherence of the international fight against terrorism. It was therefore followed by a second peer review on consequence management in response to terrorist attacks. From a critical perspective, it is shown that the impact of these peer reviews could be doubted from both a compliance and learning perspective, as monitoring and flanking measures have remained too weak. The conclusions point to additional political or normative deficits of peer reviews in EU security policy-making.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330